PENGARUH INOVASI PRODUK, EKUITAS MEREK, DAN LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN IPHONE DI KALANGAN GEN Z - Wardani, Rina Umi; Rizkina, Fanisa; Melani, Wiwik; Kusrini, Eni (Universitas Dharmawangsa, 2025)
This study aims to analyze the influence of product innovation, brand equity, and lifestyle on iPhone purchasing decisions among Gen Z. The method used is a quantitative approach with multiple linear regression techniques. Data were obtained by distributing questionnaires to Gen Z who had purchased and used an iPhone. The results of the study indicate that partially product innovation, brand equity, and lifestyle each have a positive and significant effect on purchasing decisions. In addition, simultaneously the three variables also have a positive and significant effect on iPhone purchasing decisions among Gen Z. This finding indicates that companies need to continue to innovate products, build strong brand equity, and adjust marketing strategies to consumer lifestyles to improve purchasing decisions.